2021
DOI: 10.1016/j.fastrc.2021.100012
|View full text |Cite
|
Sign up to set email alerts
|

Application of nano arthroscopy in the office setting for the removal of an intra-articular loose osseous body not identified by magnetic resonance imaging: A case report

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Multiple studies have demonstrated the utility of needle arthroscopy for numerous pathologies, both as an adjunct to standard arthroscopy and as the primary visualization instrument. [7][8][9]11 Peters et al 8 demonstrated safe use for elbow arthroscopy, while Dankert et al 12 detailed its use for loose body removal from the ankle joint. Others have demonstrated its use for more complicated procedures, such as meniscal repair or as an adjunct to anterior cruciate ligament repair.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have demonstrated the utility of needle arthroscopy for numerous pathologies, both as an adjunct to standard arthroscopy and as the primary visualization instrument. [7][8][9]11 Peters et al 8 demonstrated safe use for elbow arthroscopy, while Dankert et al 12 detailed its use for loose body removal from the ankle joint. Others have demonstrated its use for more complicated procedures, such as meniscal repair or as an adjunct to anterior cruciate ligament repair.…”
Section: Discussionmentioning
confidence: 99%
“…The Arthrex nanoscope is a zero-degree scope with a 1.9mm diameter camera. 25 The camera's resolution is 400 x 400 and displays a view of 120 degrees. 25 No other publication has reported on it's use in the talonavicular joint but it has been used successfully to remove a loose body in the ankle joint.…”
Section: Discussionmentioning
confidence: 99%
“…25 The camera's resolution is 400 x 400 and displays a view of 120 degrees. 25 No other publication has reported on it's use in the talonavicular joint but it has been used successfully to remove a loose body in the ankle joint. 25 Studies on cadaveric ankles demonstrate effective visualization with the nanoscope throughout the joint.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations